Microbiome Regulation of Autoimmune, Gut and Liver Associated Diseases - Singh, Bhagirath; Qin, Nan; Reid, Gregor (Inflammation & Allergy-Drug Targets (Discontinued), 2015)
Extensive analysis of the complexity and diversity of microbiota using metagenomics in the gut and other body sites has provided evidence that dysbiosis occurs in many disease states. With the application of next generation sequencing technology this research is starting to uncover the impact of microbiota on metabolic, physiological and immunological pathways and elucidate the cellular and molecular mechanisms involved. To highlight these advances we have focused on autoimmunity and gut and liver related diseases and discuss the opportunities and challenges of translating microbiome research towards its application in humans. Towards this goal we discuss the application of fecal microbiome transplantation (FMT) for the treatment of multiple chronic gut associated inflammatory diseases such as Clostridium difficile infection (CDI) and inflammatory bowel disease (IBD). The potential role of human migration across continents and cultures leading to alteration in their microbiome and its implication in health and disease is also discussed.
Keywords: Autoimmune diseases